SPECIAL STATUS OF AFRICAN REGIONAL STATES IN THE INTERNATIONAL SEABED AUTHORITY - Soedjianto, Felicia Ratnasari; Hanura, Marten; Zuliyan, Muhammad Arief (UI Scholars Hub, 2025)
Through the mandate of UNCLOS 1982 and the 1994 Agreement, the International Seabed Authority (ISA) exists as a regulatory regime for activities in the international seabed area. Interestingly, African countries are privileged over other countries by occupying the most seats on the ISA Council. In addition, the ISA's commitment to supporting the blue economy through the Africa Deep Seabed Resources project also accentuates the privileges of African countries. African countries' technological, financial, and knowledge capacity is minimal in seabed mining. Apart from this problem, this research aims to analyse the fundamental reasons for the ISA's actions that give privileges to African countries in international seabed mining. Using the theory of knowledge-based international regimes and the concept of productive power as analytical tools, this research finds that granting special status to African countries is driven by the formation of shared knowledge and the dominance of the productive power of African countries in the ISA. The absence of a strong superpower in establishing the ISA regime also reinforced the supremacy of productive power.